Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1115/1.4030434
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Outcome Framing and Risk Attitude in Engineering Decisions Under Uncertainty

Abstract: Decision making is a central activity in the design of an engineered system and has a significant impact on project outcomes. Although much research exists on engineering decision making, relatively little addresses behavioral aspects of how engineers make decisions. This is a potentially significant gap, as factors such as the way in which information is communicated and presented to engineers can matter greatly. For example, cognitive psychology has demonstrated that the choices people make can be strongly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, one study found that engineers react differently to gain–loss framing effects in an engineering context than was observed in general populations in other studies (Vermillion et al. 2015). A deeper understanding of how individuals make decisions in an engineering and systems design context would support prescriptive decision-making research by yielding greater insight into undesirable biases and the prescriptions that would promote rational decision-making.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, one study found that engineers react differently to gain–loss framing effects in an engineering context than was observed in general populations in other studies (Vermillion et al. 2015). A deeper understanding of how individuals make decisions in an engineering and systems design context would support prescriptive decision-making research by yielding greater insight into undesirable biases and the prescriptions that would promote rational decision-making.…”
Section: Introductionmentioning
confidence: 90%
“…However, these results often times pertain to a certain context, e.g., consumer decisions or health-related decisions (Teare et al 1994;Shiv & Fedorikhin 1999;Riva et al 2015;Kraus & Marco 2016), and it is not immediately clear how well these results translate to engineering contexts. For example, one study found that engineers react differently to gain-loss framing effects in an engineering context than was observed in general populations in other studies (Vermillion et al 2015). A deeper understanding of how individuals make decisions in an engineering and systems design context would support prescriptive decision-making research by yielding greater insight into undesirable biases and the prescriptions that would promote rational decision-making.…”
Section: Introductionmentioning
confidence: 96%
“…Thus, even fields which involve technical and statistical knowledge, which could be expected to promote "rationality", are not immune to framing and loss aversion biases. Similarly, these cognitive biases have been found to influence the decision making in a variety of fields, such as management [55], medical science [9,56], finance [57,58], engineering [59,60], law [61] and others. It is therefore likely, that MCDM problems close to any of these fields might suffer from the influence of cognitive biases.…”
Section: Implications For Mcdmmentioning
confidence: 99%